The Deep Subsurface Biosphere in Igneous Ocean Crust: Frontier Habitats for Microbiological Exploration - Edwards, Katrina; Fisher, Andrew; Wheat, C. Geoffrey (Frontiers in Microbiology, 2012)
We discuss ridge flank environments in the ocean crust as habitats for subseafloor microbial life. Oceanic ridge flanks, areas far from the magmatic and tectonic influence of seafloor spreading, comprise one of the largest and least explored microbial habitats on the planet. We describe the nature of the ridge flank crustal environments, and present a framework for delineating a continuum of conditions and processes that are likely to be important for defining subseafloor microbial "provinces." The basis for this framework is three governing sets of conditions that help to determine the nature of subseafloor biomes: crustal age, extent of fluid flow, and thermal state. We present a brief overview of subseafloor conditions, within the context of these three characteristics, for five field sites where microbial studies have been done, are underway, or have been proposed. Technical challenges remain and likely will limit progress in studies of microbial ridge-flank ecosystems, which is why it is vital to select and design future studies so as to leverage as much general understanding as possible. A characterization framework such as presented in this paper, perhaps including alternative or additional physical or chemical characteristics, is essential for achieving the greatest benefit from multidisciplinary microbial investigations of the oceanic ridge flanks.